Hyperthermic Intraperitoneal Chemotherapy and Cytoreductive Surgery in Ovarian Cancer: An Umbrella Review of Meta-Analyses - Souadka, Amine; Essangri, Hajar; Majbar, Mohammed Anass; Benkabbou, Amine; Boutayeb, Saber; You, Benoit; Glehen, Olivier; Mohsine, Raouf; Bakrin, Naoual (Frontiers in Oncology, 2022)
Background : The utility of heated intraperitoneal chemotherapy in the management of epithelial ovarian cancer (EOC) has been assessed in several randomized clinical trials and meta-analyses, and it is still a subject of controversy.Therefore, we performed an umbrella review of existing meta-analyses to summarize the outcomes of HIPEC and CRS association in ovarian cancer. Methods : We examined the MEDLINE, Cochrane Library, Scopus, Prospero, Web of Science and Science Direct from inception to May 30, 2020, for meta-analyses of randomized controlled trials and observational studies. Analyses of overall survival, disease free survival and progression survival were performed separately for primary and recurrent ovarian cancers. Results : We identified 6 meta-analyses investigating the association of HIPEC with CRS in the management of ovarian cancer. Three year overall survival was significantly improved by the association of CRS and HIPEC for primary (HR: 0.66, 95%CI :0.56-0.78 ) and recurrent ovarian cancers (HR :0.50, 95%CI :0.38-0.64). This benefit was also demonstrated on disease-free survival for primary (HR: 0.54, 95%CI :0.48-0.61 ) and recurrent ovarian cancer (HR: 0.60, 95%CI :0.46-0.78). The pooled hazard ratios confirmed the advantage of HIPEC and CRS association with respect to CRS alone on progression free survival for primary and recurrent ovarian cancer respectively with HR: 0.50, 95%CI : 0.43-0.58 and HR: 0.59, 95%CI : 0.41-0.85. Conclusions While waiting for the results of the current prospective studies, the present umbrella study suggests that HIPEC performed at the end of CRS may be a complementary effective asset for ovarian cancer patient management.